READINESS TO SELF-EDUCATION IN THE STRUCTURE OF STUDENTS’ PERSONALITY - Мartyniuk Iryna (PSYCHOLOGICAL JOURNAL, 2019)
The article analyses students’ readiness for self-education. A person’s readiness for self-education is understood as a stable psychological formation that integrates personal qualities, abilities, motivation, knowledge, skills, necessary for corresponding activities, manifests itself as a willingness to self-education and ensures its effectiveness (resulting in a qualitatively new personal state: new knowledge, skills, new personal qualities, new views and beliefs). The indicators of readiness for self-education are: understanding of the social and personal significance of self-education, a positive assessment of own need for self-education, a stable cognitive interest in a certain field of knowledge and systematic pursuits for its satisfaction, the ability to independently set self-educational goals and seek ways to resolve them, manifestation of initiatives in searching for the necessary information, working out and using it in the mastering of the relevant skills and abilities and their application, volitional efforts in the process of self-education (searching for opportunities to eliminate obstacles or find other ways to achieve the goal), a positive emotional background during self-education, emotional exaltation as a result of new knowledge, skills, meanings, etc. in the process of self-education. On the basis of the theoretical analysis of scientific sources, the personal psychological characteristics that can support development of a person’s readiness for self-education are distinguished: internal motivation for studying, motives of studying at university, the need of knowledge, understanding of education, knowledge and development as important values, general mental abilities, development of organizational abilities, reflection and meaningfulness of life. The empirical study on development of these psychological characteristics and readiness for self-education was implemented with the sample consisting on university students. In order to study the students’ readiness of for self-education, the author’s technique "Experimental Situation" was used. To study the students’ learning motivation, we used: the method diagnosing the internal learning motivation proposed by T. D. Dubovitska, the method determining the learning motives (in the modification of A. A. Rean, V. A. Yakunin), the technique "SAMOAL", Rokeach Value Survey. To diagnose the general mental abilities, Wonderlic Personnel Test (adapted by V.N.Buzin) was used. To study organizational skills, we used the scale of communicative and organizational skills. Reflection was studied with the help of the questionnaire on reflexivity of A. V. Karpov and the Test of Meaningful Life Orientation of D. A. Leontiev. Half of the respondents showed high indicators of readiness for self-education; the majority of the rest showed average results, and the small part of the respondent showed low results. The most popular motives of students’ training at university are: “to become a highly qualified specialist”, “to acquire profound and solid knowledge”, “to be successful in future professional work”. At the same time, with the increase in the level of readiness for self-education, the motive “to get intellectual pleasure” gains popularity. The existence of a weak statistically significant correlation between the respondents’ readiness to self-education and the internal motivation of the study and the very weak, but statistically significant ones with the need of cognition, attitude to cognition as a value, organizational skills, reflection and meaningfulness of life are substantiated. These correlations are regarded as an indicator of the relative independence of readiness for self-education from other (motivational, intellectual, reflexive) psychological personal characteristics. The respondents were grouped depending on bond strength between development of their psychological characteristics and readiness for self-education; and the types of students’ readiness to self-education are determined on this basis: thought-organized, supported by internal learning motivation; oriented to life-long values; intellectual (combined with higher than that for other types readiness for self-education); and reflexive. Taking these types into account at development of a system of measures to optimize the students’ readiness for self-education is a prospect of research in this direction.